Respiratory Bronchiolitis-Interstitial Lung Disease in Chronic Kidney Disease Mimicking Uremic Lung: A Case Report - Budi Yanti; Mauliza Mauliza; Debby Sofiana; Aamir Shehzad (Jurnal Respirasi, 2022)
Introduction: Uremic lung is a frequent complication of chronic kidney disease (CKD), while interstitial lung is an inflammation of the parenchyma which impairs its capacity. These two conditions manifest similar radiological features with bilateral diffuse infiltrates. Therefore, their clinical appearance and radiological lesions are often mistaken. Case: This study reported a case of a 55-year-old male patient with shortness of breath for 1 month and worsening 1 week before hospitalization. The patient had a smoking history of 30 years with severe Brinkman index, hypertension (HT), and diabetes mellitus (DM). Auscultation examination showed crackles in both lungs, while laboratory results showed anemia, leukocytosis, increased urea and creatinine levels, and radiological features of bilateral infiltrate, suggesting a uremic lung. Furthermore, the ultrasonography showed bilateral chronic pyelonephritis and was diagnosed with CKD, uremic lung, pneumonia, anemia, hypoalbuminemia, mild hypokalemia, DM, and HT. The patient was treated with regular hemodialysis three times a week, and the serial chest X-ray showed persistent bilateral infiltrates after hemodialysis. An MSCT examination was also performed, and the results showed respiratory bronchiolitis-interstitial lung disease (RB-ILD). The patient was treated with antibiotic therapy, inhaled salbutamol, systemic steroids, and mucolytics. The patient was discharged from the hospital after the respiratory complaint improved. Conclusion: Interstitial illness should be explored in uremia patients with bilateral infiltrates resembling uremic lungs and unresponsive to hemodialysis or other therapies. Risk factors for suspected interstitial lung disease should always be examined to improve patient management.